Simulation study of a many-to-one mapping for IPv6 address owner identification in an enterprise local area network - Hakiem, Nashrul; Siddiqi, Mohammad Umar; Hashum , Mohamed Rafiq (International Journal of Network Security, 2015)
Owner identification is an important aspect of improving network visibility and enhancing network security within local area networks deploying IPv6. This paper presents a simulation study for owner identification in an enterprise local area network from their IPv6 addresses. The study is based around the reverse implementation (many-to-one mapping) of a one-to-many reversible mapping. The paper reviews the many-to-one mechanism and the associated simulation software development, followed by presentation of results obtained from required functional tests. The IPv6 address data can be obtained from the output of any network monitoring software. In addition to a text format for verification, it also uses a checksum for validation which is used during the IPv6 address generation and identification. The simulation software given here can easily identify an IPv6 address owner if the IPv6 address is properly generated by the mechanism and it can display particular verification messages.